PROSES PENGOLAHAN IKAN TERI (Stolephorus sp.)DAN PEMANFAATAN LIMBAHNYA SEBAGAI BAHAN BAKU PAKAN IKAN DALAM MENDUKUNG KONSEP ZERO WASTE - Mahrus Ali; Eko Efendi; Nuning Mahmudah Noor (Universitas Mataram, 2018)
Pasaran island is well known as a center of anchovy producer in the province of Lampung, Indonesia. The total of catched fish is to 57.6 tons per month so Pasaran island was classified as fisheries cluster producing anchovies in the province of Lampung. The processing units from fishing, curing, drying, processing to marketing steps was conducted by small and medium enterprises (SME’s) from local community. They producedvarious products such as dried anchovies, packaged vacum anchovies, snack, and raw material for feed of nila and catfish from anchovies waste. Theseintegrated processing system not only increasing the added values of anchovies in Pasaran islandbut also applying zero waste concept in the processing anchovies. Thus impacted on increasing SME’s and local community incomes.